2011
DOI: 10.1158/0008-5472.can-10-3838
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIF Prolyl Hydroxylase-2 Blocks Tumor Growth in Mice through the Antiproliferative Activity of TGFβ

Abstract: Virtually all solid tumors are dependent on a vascular network to provide them with the right amount of nutrients and oxygen. In that sense, low oxygen tension or hypoxia leads to an adaptive response that is transcriptionally regulated by the hypoxia-inducible factors (HIF), which are tightly controlled by the HIF prolyl hydroxylases (PHD). In this study, we show that inhibition of the oxygen sensor PHD2 in tumor cells stimulates vessel formation but paradoxically results in a profound reduction of tumor grow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 42 publications
8
47
1
Order By: Relevance
“…The effect of Phd2 knockdown in cancer cells depends on the tumor histotype (Ameln et al, 2011;Andersen et al, 2011;Bordoli et al, 2011;Chan et al, 2009;Kamphues et al, 2012;Lee et al, 2008;Peurala et al, 2012;Su et al, 2012), while our data show a better disease outcome when the tumor stroma is insufficient for Phd2. To assess the effect of combined Phd2 inactivation in cancer cells and stromal cells, we subcutaneously injected scramble and Phd2-silenced LLC cells in R26;Phd2 +/+ and R26;Phd2 L/+ mice.…”
Section: Acute Loss Of One or Two Phd2 Alleles Enhances Chemotherapysupporting
confidence: 44%
“…The effect of Phd2 knockdown in cancer cells depends on the tumor histotype (Ameln et al, 2011;Andersen et al, 2011;Bordoli et al, 2011;Chan et al, 2009;Kamphues et al, 2012;Lee et al, 2008;Peurala et al, 2012;Su et al, 2012), while our data show a better disease outcome when the tumor stroma is insufficient for Phd2. To assess the effect of combined Phd2 inactivation in cancer cells and stromal cells, we subcutaneously injected scramble and Phd2-silenced LLC cells in R26;Phd2 +/+ and R26;Phd2 L/+ mice.…”
Section: Acute Loss Of One or Two Phd2 Alleles Enhances Chemotherapysupporting
confidence: 44%
“…This has also been underscored by recent work from our group showing that silencing of PHD2 in several tumor lines typically leads to reduced tumor growth. 39 In mice, we (K.F. and B.W., unpublished data, October 2011) and others 14 have shown that PHD2 heterozygosity only results in a very mild form of erythrocytosis whereas global inactivation just before or after birth leads to severe and lethal polycythemia.…”
Section: Discussionmentioning
confidence: 89%
“…How PHD2 can be downregulated in some tumours whilst acting as an oncogene in others [40] remains unclear [41]. Mutations in PHD2 associated with increased risk of tumours have been reported [42] and epigenetic silencing has been proposed for PHD3 [43].…”
Section: Phd2 Integration Of Lactate-driven Angiogenesismentioning
confidence: 99%